Inhibition of the metalloprotease ADAM19 as a novel senomorphic strategy to ameliorate gut permeability and senescence markers by modulating senescence-associated secretory phenotype (SASP). - Bar, S.; Hilsabeck, T.A.U.; Pattavina, B.; López-Domínguez, J.A.; Basisty, N.; Bons, J.; Watson, M.; Schilling, B.; Campisi, J.; Kapahi, P.; Sharma, A. (Aging, 2025)
Accumulation of DNA damage can accelerate aging through cellular senescence. Previously, we established a Drosophila model to investigate the effects of radiation-induced DNA damage on the intestine. In this model, we examined irradiation-responsive senescence in the fly intestine. Through an unbiased genome-wide association study (GWAS) utilizing 156 strains from the Drosophila Genetic Reference Panel (DGRP), we identified meltrin (the drosophila orthologue of mammalian ADAM19) as a potential modulator of the senescence-associated secretory phenotype (SASP). Knockdown of meltrin resulted in reduced gut permeability, DNA damage, and expression of the senescence marker ?-galactosidase (SA-?-gal) in the fly gut following irradiation. Additionally, inhibition of ADAM19 in mice using batimastat-94 reduced gut permeability and inflammation in the gut. Our findings extend to human primary fibroblasts, where ADAM19 knockdown or pharmacological inhibition decreased expression of specific SASP factors and SA-?-gal. Furthermore, proteomics analysis of the secretory factor of senescent cells revealed a significant decrease in SASP factors associated with the ADAM19 cleavage site. These data suggest that ADAM19 inhibition could represent a novel senomorphic strategy.